A ‘marca’ da ressurreição de Jesus na História da Humanidade - Ambrosio, Juan (2008)
The author follows a path divided into three moments. In the first moment, and starting from a more anthropological thinking, he seeks to show how the opening to the Transcendence (to Christians the opening to the Personal Mystery of God) makes integrant part of the human condition, in such a way that the concreteness of that opening allows to live the existence assuming all its possibilities. In the second moment, he seeks to reflect how the opening to human makes part of God’s own project. In this context, he looks to Jesus Christ to show how in Him both previous movements are simultaneously formed. In the third and last moment, and from the answers to four questions (What can I know? What can I expect? What do I have to do? What can I celebrate?) he seeks to take out consequences to the living in faith, searching in that living for evidence of the ‘sign’ of Jesus’ resurrection in the history of mankind.